Unraveling the Fintech Landscape: A Systematic Mapping Study on the Impact of Financial Technology Innovation on Investment Decision-Making in ASEAN Banking - Mohammad Benny Alexandri; Irton Usman; Umi Narimawati; Agus Taryana (UIN Sunan Gunung Djati, 2023)
This systematic mapping study identifies and analyses fintech innovations that influence investment decision-making in ASEAN banking. Through a rigorous literature search and screening process, 128 relevant studies were analyzed, identifying four key fintech innovations that impact investment decision-making in ASEAN banking: advisory platforms, blockchain technology, peer-to-peer lending, and mobile banking. The analysis of these innovations reveals their potential to improve investment decision-making in terms of cost efficiency, speed, accessibility, and transparency. However, the study also identified several challenges associated with these innovations, including cybersecurity risks, regulatory issues, and a lack of customer trust. This study provides valuable insights into the current state of fintech innovation in ASEAN banking and its impact on investment decision-making. The findings can help policymakers, regulators, and financial institutions make informed decisions about developing and adopting fintech innovations in the region.